1998
DOI: 10.1021/ie980198k
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiltration Mass Transfer at the Entrance Region of a Slit Laminar Flow

Abstract: A numerical model to predict laminar flows hydrodynamics and concentration polarization of salt aqueous solutions in a slit is proposed and experimentally validated. Physical modeling for the flow and for the mass transfer process is incorporated, in association with the osmotic pressure constitutive equation and a variation law for the membrane intrinsic rejection coefficient. The finite volume formulation is used with the SIMPLE algorithm to solve the discretized equations derived from the partial nonlinear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…8b) and for the permeation flux v p = 1.5×10 −5 m/s. Once the permeation flux is kept unchanged for both cases, the flow develops more slowly, as expected, for the largest value of the circulating Reynolds number, Re = 1000, similarly to what occurred in NF systems described by Geraldes et al (1998). Fig.…”
Section: Hydrodynamic Boundary Layer: Entrance Length Predictionssupporting
confidence: 71%
See 1 more Smart Citation
“…8b) and for the permeation flux v p = 1.5×10 −5 m/s. Once the permeation flux is kept unchanged for both cases, the flow develops more slowly, as expected, for the largest value of the circulating Reynolds number, Re = 1000, similarly to what occurred in NF systems described by Geraldes et al (1998). Fig.…”
Section: Hydrodynamic Boundary Layer: Entrance Length Predictionssupporting
confidence: 71%
“…They concluded that, for typical UF permeation velocities ranging from 10 −6 to 10 −5 m/s, suction has no significant effects and the hydrodynamic entrance length is practically invariant. Geraldes et al (1998) and performed a set of numerical simulations for the asymmetric nanofiltration (NF) in a slit, in order to evaluate the effect of permeation rates on the hydrodynamic entrance length and on the momentum and concentration boundary layer growth. They concluded that the typical permeation velocities encountered in NF do not affect the hydrodynamic boundary layer development, i.e., the entrance length does not vary with the permeation velocity, although it may affect the onset of the concentration boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…The tangential flow filtrations were performed in a cell unit described previously [23] with a slit-type (20 cm × 3 cm × 0.2 cm) feed channel and an effective membrane area of 60 cm 2 . The membranes were first compacted through pure water recirculation at a pressure of 30 bar for 3 h and characterized through the determination of the hydraulic permeabilities, observed retentions to reference solutes, R obs, and MWCO.…”
Section: Membrane Preparation and Characterizationmentioning
confidence: 99%
“…The Grober equation is an empirical correlation, but it can also be obtained from the boundary layer model that assumes an impermeable wall and low mass transfer rates. Geraldes et al [25,26], have shown that the momentum boundary layer growth is independent of the permeation fluxes in the range of interest of nanofiltration (0.2 × 10 −5 m/s < J v < 3 × 10 −5 m/s). Therefore, those assumptions do not influence the hydrodynamics boundary layer, and Eq.…”
Section: M20 [24]mentioning
confidence: 99%